2010
DOI: 10.1021/jp107873w
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Studies on Photoisomerizations of (6−4) and Dewar Photolesions in DNA

Abstract: The (6-4) photoproduct ((6-4) PP) is one of the main lesions in UV-induced DNA damage. The (6-4) PP and its valence isomer Dewar photoproduct (Dewar PP) can have a great threat of mutation and cancer but gained much less attention to date. In this study, with density functional theory (DFT) and the complete active space self-consistent field (CASSCF) methods, the photoisomerization processes between the (6-4) PP and the Dewar PP in the gas phase, the aqueous solution, and the photolyase have been carefully exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
22
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 48 publications
1
22
0
2
Order By: Relevance
“…[15] Light absorption of the pyrimidinone moiety induces a secondary photochemical reaction-the formation of a Dewar valence isomer ( Figure 1). [9,[16][17][18] Due to the higher spectral intensity mentioned above, and a rather high quantum yield of % 0.02, most (6-4) lesions eventually transform into Dewar lesions under solar illumination. [9] As part of an effort to study the Dewar formation, herein we report the photophysical properties of the pyrimidinone chromophore.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[15] Light absorption of the pyrimidinone moiety induces a secondary photochemical reaction-the formation of a Dewar valence isomer ( Figure 1). [9,[16][17][18] Due to the higher spectral intensity mentioned above, and a rather high quantum yield of % 0.02, most (6-4) lesions eventually transform into Dewar lesions under solar illumination. [9] As part of an effort to study the Dewar formation, herein we report the photophysical properties of the pyrimidinone chromophore.…”
Section: Introductionmentioning
confidence: 99%
“…For 5-methyl-2-(1H)-pyrimidinone the conical intersection between the primarily excited pp* state and the ground state was predicted to lie 2300-3400 cm À1 above the pp* minimum. [20] Further, a very recent ab initio study [17] on the pyrimidinone chromophore in the (6-4) lesion predicts an energy difference of % 2000 cm…”
mentioning
confidence: 99%
“…1 This fast relaxation prevents the creation of UV damage. [10][11][12][13] The most frequent photoreaction of nucleic acids is an intra-1038 RISTIĆ, PETKOVIĆ and ETINSKI strand pyrimidine dimerization. [2][3][4][5] Recent theoretical work [6][7][8] and supersonic jet experiments 4 have shown that this dark state is the T 1 state.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous work showed that the isomerization from T(dew)T to T(6-4)T in the neutral ground state has a very high barrier (about 30 kcal/mol), while it is sharply reduced to 15 kcal/ mol when one electron is injected. 21 In the current study, several enzymatic repair pathways are studied by the density functional theory method. From our calculations, the rearrangement of the Dewar lesions into the corresponding (6-4) lesions with electron injection was validated as the most efficient repair pathway.…”
Section: Introductionmentioning
confidence: 99%